Epigenetic reprogramming for targeting IDH-mutant malignant gliomas - Park, Jongwhi; Turcan, S̨evin (Cancers, 2019)
Targeting the epigenome has been considered a compelling treatment modality for several cancers, including gliomas. Nearly 80% of the lower-grade gliomas and secondary glioblastomas harbor recurrent mutations in isocitrate dehydrogenase (IDH). Mutant IDH generates high levels of 2-hydroxyglutarate (2-HG) that inhibit various components of the epigenetic machinery, including histone and DNA demethylases. The encouraging results from current epigenetic therapies in hematological malignancies have reinvigorated the interest in solid tumors and gliomas, both preclinically and clinically. Here, we summarize the recent advancements in epigenetic therapy for lower-grade gliomas and discuss the challenges associated with current treatment options. A particular focus is placed on therapeutic mechanisms underlying favorable outcome with epigenetic-based drugs in basic and translational research of gliomas. This review also highlights emerging bridges to combination treatment with respect to epigenetic drugs. Given that epigenetic therapies, particularly DNA methylation inhibitors, increase tumor immunogenicity and antitumor immune responses, appropriate drug combinations with immune checkpoint inhibitors may lead to improvement of treatment effectiveness of immunotherapy, ultimately leading to tumor cell eradication.